Application of Mung Bean Biocoagulant for Tofu and Tempeh Wastewater Treatment - Ismi Khairunnissa Ariani; Rina Noor Hayati; Sukma Agustina; Riza Hudayarizka (Darul Yasin Al Sys, 2026)
Wastewater generated from tofu and tempeh production commonly contains high organic loads and suspended particles, necessitating environmentally sustainable treatment methods. This study investigated the use of mung bean (Vigna radiata) as a biocoagulant for reducing chemical oxygen demand (COD) and turbidity and improving the pH of tofu and tempeh wastewater. The study evaluated the effect of extraction with 1 M NaCl on biocoagulant performance, determined the optimum biocoagulant dosage, and assessed the influence of slow-mixing time on treatment effectiveness. Coagulation–flocculation was performed using mung bean biocoagulants before and after NaCl extraction, with dosages ranging from 1 to 5 g per 500 mL of wastewater and slow-mixing times ranging from 15 to 35 minutes. Initial characterization indicated that several wastewater quality parameters exceeded the applicable discharge standards. The NaCl-extracted biocoagulant performed better than the unextracted biocoagulant, achieving COD and turbidity removal efficiencies of 9.95% and 90.98%, respectively, with a final pH of 7.27. Across the dosage variations, the highest COD removal efficiency of 41.45% was obtained at 4 g/500 mL, whereas the highest turbidity removal efficiency of 91.17% was achieved at 2 g/500 mL. The highest final pH of 7.81 was recorded at 5 g/500 mL. The optimum slow-mixing time was 15 minutes, resulting in COD removal of 14.26%, turbidity removal of 87.45%, and a final pH of 7.19. These findings demonstrate that NaCl-extracted mung bean biocoagulant has considerable potential for improving tofu and tempeh wastewater quality, particularly through turbidity removal. The study contributes to the development of plant-based biocoagulants as an environmentally sustainable alternative for wastewater treatment, although optimization remains necessary to improve COD removal efficiency.